Effects of caffeine intake and smoking on neurocognition in schizophrenia. Issue 3 (30th December 2015) - Núñez, Christian; Stephan-Otto, Christian; Cuevas-Esteban, Jorge; Maria Haro, Josep; Huerta-Ramos, Elena; Ochoa, Susana; Usall, Judith; Brébion, Gildas
Abstract: Although most studies support the beneficial effects of caffeine on neurocognition, its effects have never been assessed in psychiatric patients. In addition, results from studies in smokers are contradictory. Moreover, there are no data available about the neurocognitive effects of caffeine and tobacco together. We explored the concomitant effects of regular caffeine and tobacco intake on neurocognition in 52 schizophrenic patients and 61 healthy controls. Verbal fluency, processing speed, and working, visual and verbal memory were assessed. For each measurement, two tasks with two levels of complexity were administered. Our results showed that caffeine intake had beneficial effects on male schizophrenic patients only in complex tasks requiring deeper cognitive processing (semantic fluency, cognitive speed, working memory, and visual memory). Female patients and controls were unaffected. In contrast, smoking had a negative effect on male, but not on female, schizophrenic patients in semantic fluency. The effects of smoking in controls were inconsistent. In conclusion, our data showed, for the first time, beneficial effects of caffeine intake on neurocognition in male schizophrenic patients. These data suggest that further research of therapeutics based on caffeine is needed, as this could be beneficial for schizophrenic patients. In contrast, smoking appears to be detrimental. Highlights: This is the first study to explore effects of caffeine and tobacco together. Caffeine intake improved neurocognitinion in male schizophrenic patients. Caffeine intake seemed to improve only when patients performed complex tasks. Smoking had negative effects on neurocognition in male schizophrenic patients. Females appeared to be less affected by caffeine intake and smoking.